2011
DOI: 10.1007/s12160-011-9315-8
|View full text |Cite
|
Sign up to set email alerts
|

Applied Tension and Coping with Blood Donation: A Randomized Trial

Abstract: The results of this study suggest that the effects of applied tension on vasovagal symptoms are not mediated entirely by exercise-related changes in blood pressure and heart rate. Rather, it may reduce anxiety or physiological consequences of anxiety. Applied tension is a useful treatment which can help people cope during blood donation and other invasive medical interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…Eight trials included AMT implemented using a number of different methods during donation as an intervention (Ditto et al , 2003a,b; Ditto & France, ; Ditto et al , , ; Kowalsky et al , ; Holly et al , ; Ditto et al , ). In one trial, 500 mL water was given prior to donation as a co‐intervention.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eight trials included AMT implemented using a number of different methods during donation as an intervention (Ditto et al , 2003a,b; Ditto & France, ; Ditto et al , , ; Kowalsky et al , ; Holly et al , ; Ditto et al , ). In one trial, 500 mL water was given prior to donation as a co‐intervention.…”
Section: Resultsmentioning
confidence: 99%
“…The primary outcomes of this review, namely rate of donor syncope and rate of donor return for subsequent donation, were poorly reported. Donor syncope was included as an outcome in five trials (Sauer & France, ; Ditto et al , , ; Holly et al , ; van den Berg et al , ) but only one of these (van den Berg et al , ) reported rates of syncope separately for each trial arm and one trial (Sauer & France, ) did not report results. Rates of return for subsequent donation were reported in four trials, after 1 year (Ditto et al , ; France et al , ) and 2 years (Ditto et al , , ) although one trial did not report results separately for each trial arm (France et al , ) and one trial presented results graphically with no sample sizes provided (Ditto et al , ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations